2021
DOI: 10.3390/app112210925
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Sliding Mode Control of Vehicle Magnetorheological Semi-Active Air Suspension

Abstract: In order to reduce vehicle vibration during driving conditions, a fuzzy sliding mode control strategy (FSMC) for semi-active air suspension based on the magnetorheological (MR) damper is proposed. The MR damper used in the semi-active air suspension system was tested and analyzed. Based on the experimental data, the genetic algorithm was used to identify the parameters of the improved hyperbolic tangent model, which was derived for the MR damper. At the same time, an adaptive neuro fuzzy inference system (ANFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…(7) In order to take the coordination, response speed, steady-state accuracy, overshoot and other performance of the control system into account 36 , when τ 1 > 1 , let τ 1 = 1 , and τ 2 = τ 3 = τ 4 = τ 1 . Substituting the real-time contracting-expanding factor parameters into Eq.…”
Section: A Novel Scaling Factor Controllermentioning
confidence: 99%
“…(7) In order to take the coordination, response speed, steady-state accuracy, overshoot and other performance of the control system into account 36 , when τ 1 > 1 , let τ 1 = 1 , and τ 2 = τ 3 = τ 4 = τ 1 . Substituting the real-time contracting-expanding factor parameters into Eq.…”
Section: A Novel Scaling Factor Controllermentioning
confidence: 99%
“…In addition, a control strategy using a novel conditional function was proposed, and it was experimentally shown that the desired performance can be achieved, which has great potential in terms of control strategies (Bagherkhani and Mohebbi, 2022; Deng et al, 2022c; Nagamatsu and Shiraishi, 2022). For better control of magnetorheological dampers for air suspension, a fuzzy sliding mode control strategy is proposed, and the simulation analysis structure shows that this strategy has a great improvement in performance for semi-active air suspension (Li et al, 2021a). The main reason for the hysteresis characteristics of magnetorheological dampers is the compressibility of MR fluid.…”
Section: Introductionmentioning
confidence: 99%
“…As the key to achieve adaptive performance of MR intelligent suspension, the design of control algorithm in MR intelligent suspension research is the core issue. A series of control algorithms are proposed by researchers, including skyhook control algorithm [6], LQR control algorithm [7,8], neural network control algorithm [9,10], fuzzy control algorithm [11,12], robust control [13], human simulated intelligent control algorithm [14] and PID control algorithm [15,16] and so on. These algorithms usually take the absolute velocity of the sprung mass and relative velocity of the damper as the feedback variables of the controller, and the absolute velocity are obtained by acceleration integral.…”
Section: Introductionmentioning
confidence: 99%